Neurobiological Correlates of Personality-Driven Psychosomatic Reactivity: A Psychoneuroimmunological Perspective - Avilés-Santa , Daymar; Wandzilak , Przemyslaw; Péloquin , Derek; Critchley , Sue J (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to examine an integrated psychoneuroimmunological model linking personality traits to psychosomatic reactivity through perceived stress, neuroendocrine activity, and immune activation. A cross-sectional correlational design was employed with a community-based adult sample recruited from urban health centers in Mexico. Participants completed validated self-report measures assessing personality traits, perceived stress, and psychosomatic symptoms. Neuroendocrine activity was indexed using salivary cortisol collected at awakening and 30 minutes post-awakening, while immune activation was assessed through serum inflammatory markers, including interleukin-6 and C-reactive protein. Data were analyzed using correlation analyses, multiple regression models, mediation analyses with bootstrapping, and structural equation modeling to test direct and indirect pathways among psychological and biological variables. Inferential analyses indicated that neuroticism was a strong positive predictor of psychosomatic symptoms, whereas conscientiousness and agreeableness were significant negative predictors. Perceived stress significantly mediated the relationship between neuroticism and psychosomatic symptom severity. Elevated cortisol awakening response was associated with higher perceived stress and greater somatic symptom burden and functioned as an additional mediator. Inflammatory markers were positively associated with cortisol activity and psychosomatic symptoms. Structural equation modeling demonstrated good model fit and supported a sequential pathway from personality traits to stress appraisal, neuroendocrine dysregulation, immune activation, and psychosomatic reactivity, with protective traits exerting indirect buffering effects through reduced stress responses. The findings support a psychoneuroimmunological model in which personality traits function as central regulators of psychosomatic reactivity by shaping psychological stress appraisal and downstream neuroendocrine and immune processes, highlighting the importance of integrative, personality-informed approaches to psychosomatic health.